Speech Recognition pada Kontrol Gerak Tangan Bionik berbasis Raspberry Pi dan Arduino - Syaiful Mansyur; Muchamad Malik; Aan Burhanuddin; Jihan Abdul Malik (Jurnal Engine: Energi, Manufaktur, dan Material, 2023)
The bionic hand is a broad bio-mechatronic device that incorporates various concepts involving biology and mechatronics. In this journal, the authors research finger movements in bionic hands using voice commands. In designing this bionic hand, the author made a mechanical design using a 3D printing machine. The hardware design used by the Raspberry Pi to process voice data is then transmitted to Arduino to carry out servo movement commands so that it can move bionic fingers. Software design uses the Python language using the Google text-to-speech API. From this research, data was generated with 100% accuracy. The movement of bionic fingers moves according to the commands spoken.